Competitive Effects of Iron, Zinc, and Cadmium Ions on Lead Removal from Aqueous Solutions Using the Nanostructured Ash Cedar Absorbent - Lale Divband; Saeid Broomand nasab; Pooya Shirazi; Saeid Bibak Hafshejani; Roya Mafi Gholami (آب و فاضلاب, 2015)
The objective of this study was to determine the efficiency of lead removal from aqueous (both single- and multi-element) solutions using the nanostructured ash cedar absorbent. Nanostructured ash cedar was synthesized and the effects of pH, absorbent dosage, and contact time on lead removal efficiency were investigated in a batch system. The absorbent was characterized by SEM, PSA, XRF, and FTIR. SEM results showed that all the particles had diameters smaller than 207 nm. It was also found that the optimum pH values for lead adsorption were 6 and 5 for the single-element and the multi-element systems, respectively. The maximum removal efficiencies of 94% and 98% and maximum adsorption capacities of 27 mg/g and 21 mg/g were obtained for the single- and multi-element systems, respectively. Comparison of the Freundlich, Langmuir, and Sips isotherms showed that the Langmuir model with R2 =0.99 and RMSE = 1.01 for the single element system described the adsorption data better than other models did. Also, this model with R2 = 0.99) and RMSE = 0.024 better fitted the adsorption data in the multi-element system.